Aberrant Chloride Intracellular Channel 4 Expression Is Associated With Adverse Outcome in Cytogenetically Normal Acute Myeloid Leukemia - Huang, Sai; Huang, Zhi; Chen, Ping; Feng, Cong (Frontiers in Oncology, 2020)
Background and Methods: Acute Myeloid Leukemia, starts in the bone marrow, is a group of the hematopoietic stem cell disorders. Chloride Intracellular Channel 4 (CLIC4) is regulated by p53, c-Myc and TGF-β. It induces the NF-kB-dependent activation of HIF (hypoxia-inducible factor) and participates in tumor growth though its microenvironmental function. However, its prognostic value in AML remains unclear as well as its co-expression biomarkers. In this study, we evaluated the prognostic significance of CLIC4 expression using two independent large cohorts of CN-AML patients. Multivariable analysis and multi-omics analysis with weighted correlation network analysis in CN-AML group were also presented. Based on the CLIC4 and its related genes, microRNA-target gene interaction network analysis and downstream gene ontology analysis was performed to unveil the complex functions behind CLIC4. Results: We demonstrated overexpression of CLIC4 was notably associated with unfavorable outcome in two independent cohorts of CN-AML patients (OS & EFS: P < 0.0001, n = 185; OS: P = 0.016, n = 232), as well as in European Leukemia Net Intermediate-I group (OS: P = 0.015, EFS: P = 0.012, n = 115), National Comprehensive Cancer Network Intermediate Risk AML group (OS & EFS: P < 0.0001, n = 225), and non-M3 AML group (OS & EFS: P < 0.0001, n = 435). Multivariable analysis further validated CLIC4 as a high-risk factor in CN-AML group. Multi-omics analysis presented overexpression of CLIC4 was associated with co-expression of different gene sets in leukemia, up/down-regulation of immune-related pathways, dysregulation of microRNAs, and hypermethylation around the CpG islands, in open sea regions, and different gene structural fragments including TSS1500, gene body, 5’UTR region, 3’UTR region and 1st Exon. By further performing weighted correlation network analysis on multi-omics data, certain biomarkers that co-expressed with CLIC4 were also unveiled. Conclusions: We demonstrated CLIC4 is potentially a novel, potential unfavorable prognosticator and therapeutic target for CN-AML. As a key role in CN-AML, the interactions between CLIC4 and other genomics and transcriptomics data was confirmed by performing microRNA-target gene interaction network analysis and gene ontology enrichment analysis. The experimental result provides evidence for clinical strategy selection of CN-AML patients.